Labor Market Externalities of Pre-Retirement Employment Protection - Pawel Chrostek; Krzysztof Karbownik; Michal Myck (Center for Economic Studies and ifo Institute (CESifo), 2024)
Using population-level administrative data, we study labor market externalities stemming from age-specific employment protection legislation (EPL) targeted towards older workers. Our results show no economically meaningful overall effects of the EPL on employment or earnings of either men or women approaching eligibility. Considering separately incumbent workers and non-employees we find small positive and small negative employment effects for the former and the latter groups, respectively.
Keywords: J63; J21; J23; 330; employment protection; older workers; externalities; labor demand